2017
DOI: 10.1016/j.ymgme.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in glucosylsphingosine (lyso-Gb1) in treatment-naïve and previously treated patients receiving velaglucerase alfa for type 1 Gaucher disease: Data from phase 3 clinical trials

Abstract: Gaucher disease (GD), an autosomal recessive lipid storage disorder, arises from mutations in the GBA1 (β-glucocerebrosidase) gene, resulting in glucosylceramide accumulation in tissue macrophages. Lyso-Gb1 (glucosylsphingosine, lyso-GL1), a downstream metabolic product of glucosylceramide, has been identified as a promising biomarker for the diagnosis and monitoring of patients with GD. This retrospective, exploratory analysis of data from phase 3 clinical trials of velaglucerase alfa in patients with type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 33 publications
4
53
3
3
Order By: Relevance
“…Using the NICE STA method, risk of bias in the sole randomized controlled trial was deemed low, although bias regarding the allocation concealment process and between-group baseline similarities was unclear ( Table S1 ) [ 36 ]. Thirty non-randomized clinical trials and observational studies with full-study reporting were assessed using the Newcastle–Ottawa scoring tool [ 3 , 26 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], of which 19 were deemed to have a high risk of bias (score 0–3; Table S2 ). Thirty-two animal studies were assessed using the SYRCLE risk of bias tool [ 45 , 53 , 58 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the NICE STA method, risk of bias in the sole randomized controlled trial was deemed low, although bias regarding the allocation concealment process and between-group baseline similarities was unclear ( Table S1 ) [ 36 ]. Thirty non-randomized clinical trials and observational studies with full-study reporting were assessed using the Newcastle–Ottawa scoring tool [ 3 , 26 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], of which 19 were deemed to have a high risk of bias (score 0–3; Table S2 ). Thirty-two animal studies were assessed using the SYRCLE risk of bias tool [ 45 , 53 , 58 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies provided information relevant to the diagnosis of GD [ 3 , 26 , 33 , 38 , 40 , 41 , 44 , 46 , 47 , 49 , 50 ]. Normally, lyso-Gb1 is undetectable or found at trace levels in plasma (i.e., <4.9 ng/mL (10.61 nmol/L)) and tissue [ 39 , 114 ]. Data from five prospective observational studies indicated consistently that lyso-Gb1 in plasma and red blood cell (RBC) membranes were higher in untreated patients with GD than in control subjects ( Table 4 ) [ 3 , 26 , 40 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations